Postnatal ontogeny of the spine of the Emperor Penguin Aptenodytes forsteri (Aves, Sphenisciformes) and modularity of the neck - Sosa, María Alejandra; Acosta Hospitaleche, Carolina Ileana Alicia (Polar Biology)
The Emperor Penguin (Aptenodytes forsteri), the largest extant penguin, inhabits exclusively in Antarctica. Little is known about the spine of this species; this work presents a description of the vertebral column of an adult of A. forsteri, compared with specimens from different ontogenetic stages (chick, fledgling, and juvenile). We also analyze the regionalization of the spine with a principal component analysis (PCA), and the modularity with an elliptical Fourier analysis, performing a PCA, followed by a linear discriminant analysis on the PC scores. Our results show that the vertebrae are completely ossified in adults, while the suture lines between the different elements are visible in the previous stages and some structures remain cartilaginous. A total of 42/43 vertebrae were counted (13 cervicals, 2 cervicothoracics, 6/7 thoracics, 13 synsacrals, and 8 caudals), and an extra vertebra appears in the thoracic region of one specimen. These regions are already differentiated in fledglings, but not in chicks. Six modules associated with the S-shape of the adult neck were recognized and are represented by different numbers of vertebrae: module 1 (C1), module 2 (C2), module 3 (C3–5), module 4 (C6), module 5 (C7–9) and module 6 (C10–13). Differences in the vertebral configuration in modules 5 and 6 of previous stages were found, where cervical 10 is part of module 5 due to the absence of the processus ventralis corporis. Fil: Sosa, María Alejandra. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina